Correlation of EEG biomarkers of cannabis with measured driving impairment. (25th November 2019) - Brown, Timothy; McConnell, Marissa; Rupp, Greg; Meghdadi, Amir; Richard, Christian; Schmitt, Rose; Gaffney, Gary; Milavetz, Gary; Berka, Chris
Abstract: Objective: The objective of this study was to use electroencephalogram (EEG) biomarkers derived from a short, easily administered neurocognitive testbed to determine acute cannabis intoxication and its effect on driving performance in a driving simulator. Methods: The data analyzed were from a study examining the relationship between psychomotor task performance, EEG data, and driving performance in a simulator. EEG data were collected using a STAT® X-24 EEG Wireless Sensor Headset, which was worn during the psychomotor and driving tasks. Driving data were collected for segments of consistent driving environments, including urban driving, urban curves, interstate, interstate curves, dark rural, and rural straightaways. Dependent measures included measures of lateral and longitudinal vehicle control. Results: There was a significant relationship between impaired driving performance as indicated by increased standard deviation of lane position and EEG power in slow theta band (3–5 Hz) in parietal and occipital areas. Conclusions: These results, combined with our prior reported results, suggest that EEG and electrocardiogram (ECG) acquired concurrent with neuropsychological tests hold potential to provide a highly sensitive, specific, and dose-dependent profile of cannabis intoxication and level of impairment.